2018
DOI: 10.15575/biodjati.v3i2.3204
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Seed Coating with Trichoderma sp. and Application of Bokashi Fertilizer to the Quality of Soybean (Glycine max. L) Seed

Abstract: The decrease of soybean productivity was caused by low quality of seed. To improve the quality of seed, soybean seed were coated  with Trichoderma sp. and adding bokashi organic fertilizer. This research aimed at finding the best dose combination of Trichoderma sp.  and bokashi fertilizer to improve the quality of soybeans. The research was conducted in the experiment field and Laboratory of Seed Technology at Padjadjaran University in April - August 2017. The experimental design in this research was Randomize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…As a result, the rise in shoot fresh weight following IBA treatment may be attributable to increases in shoot length, leaf area, and leaf fresh weight. These results are consistent with previous studies which observed that the application of IBA promoted plant and shoot length, plant height, and dry weight of both branches and leaves (Umadi et al, 2018). The findings of the current study demonstrated that IBA treatment increased the length, weight, and number of shoots on soybean plants.…”
Section: Discussionsupporting
confidence: 93%
“…As a result, the rise in shoot fresh weight following IBA treatment may be attributable to increases in shoot length, leaf area, and leaf fresh weight. These results are consistent with previous studies which observed that the application of IBA promoted plant and shoot length, plant height, and dry weight of both branches and leaves (Umadi et al, 2018). The findings of the current study demonstrated that IBA treatment increased the length, weight, and number of shoots on soybean plants.…”
Section: Discussionsupporting
confidence: 93%
“…According to [23], seed yield does not depend on the number of prospective seeds processed into clean seeds but is determined by the quality of the processed seeds. Umadi et al [24] state that observation on the weight of 100 seeds, the treatment combination generally had more significant results than the weight of 100 grain in the description of Anjasmoro varieties of soybean plants (14.8-15.3g/100 seeds). The importance of 100 seeds sources in their experiment range from 14.53 to 17.23 g/100 roots, which meant that the size of the seed was large (>14 g/100 seeds).…”
Section: Soybean Production At the Study Sitementioning
confidence: 99%